Hollow Nanospheres: Engineering Iron Oxide Hollow Nanospheres to Enhance Antimicrobial Property: Understanding the Cytotoxic Origin in Organic Rich Environment (Adv. Funct. Mater. 30/2016). (8th August 2016) - Nor, Yusilawati Ahmad; Zhou, Liang; Meka, Anand Kumar; Xu, Chun; Niu, Yuting; Zhang, Hongwei; Mitter, Neena; Mahony, Donna; Yu, Chengzhong
Abstract : On page 5408, C. Yu and co‐workers describe engineering of iron oxide hollow nanospheres that successfully combine high antimicrobial activity with an excellent safety profile toward mammalian cells. The porous structure of the nanospheres adds the potential use as a drug delivery vehicle, rendering the approach promising for battling widespread bacterial infections.